A música como importante ferramenta de trabalho com dependentes químicos internados em um CAPS AD do Distrito Federal: relato de experiência (Research, Society and Development, 2023)
The psychiatric reform brought a new perspective of care for people with mental disorders in Brazil. With the proposal to reduce isolation and hospitalizations in psychiatric hospitals, Psychosocial Care Centers appear, opening space for interdisciplinary work focused on psychosocial rehabilitation and this includes individuals in mental suffering due to the use of chemical substances. It is in this context that workshops and therapeutic groups function as tools that can help users manage the damage caused by a mental disorder and maximize the potential that facilitates better psychological and social performance. This experience report tells about the experience of a resident psychologist who participated in a music group held in a CAPS AD III in the Distrito Federal with chemically dependent individuals who were hospitalized in this service, and aims to highlight the importance of music as a working tool with these individuals, opening up a discussion about the possibilities of music in the care provided to users of mental health services.